THE EFFECT OF BOARD GAME TO INCREASE ENGLISH VOCABULARYMASTERY: SYSTEMATIC REVIEW - Ubaidatur Rahmah Khodijah Al-Jawwadah; Tiyas Saputri (Universitas Islam Balitar, 2021)
The aims of this study were: (1) to find out the effect of board game to increase English vocabulary mastery and (2) to find out which level of education can apply board game by collecting several sources related to the use of board game in learning English. This study used systematic review method. To collect the data, this study used documentations. The data in this study were 10 sources which consisted of 4 theses and 6 articles. In analyzing the data, this study used descriptive analysis. The results presented the significance differences before and after getting the treatment by using board game. It can be seen from the post-test scores that presented better than the pre-test scores. Therefore, board game is effective to increase students’ vocabulary mastery. Moreover, it can be applied in all levels of education.